2020
DOI: 10.1039/d0ee01680b
|View full text |Cite
|
Sign up to set email alerts
|

Highly active and thermally stable single-atom catalysts for high-temperature electrochemical devices

Abstract: Single-atom catalysts provide unique catalytic properties and maximize atom utilization efficiency. While utilizing them at elevated temperatures is highly desirable, their operating temperature is usually kept below 300°C to prevent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 137 publications
3
29
0
Order By: Relevance
“…Theoretical studies revealed that the extremely high stability originated from the significant CMSIs formed between the positively charged Au SAs with the FeO x support. [ 51 ] Similar phenomena were also evidenced for Pt 1 /FeO x , [ 7,52 ] Pt 1 /CeO 2 , [ 53 ] Au 1 /CeO 2 , [ 54 ] Ir 1 /FeO x , [ 55 ] and other M 1 /FeO x . [ 56 ] For carbon‐based substrates, the coordination environment of SAs including the coordination mode and coordination strength directly influences the interaction between metal atoms and substrates.…”
Section: Constructing Strategies Of Environmental Sacssupporting
confidence: 62%
“…Theoretical studies revealed that the extremely high stability originated from the significant CMSIs formed between the positively charged Au SAs with the FeO x support. [ 51 ] Similar phenomena were also evidenced for Pt 1 /FeO x , [ 7,52 ] Pt 1 /CeO 2 , [ 53 ] Au 1 /CeO 2 , [ 54 ] Ir 1 /FeO x , [ 55 ] and other M 1 /FeO x . [ 56 ] For carbon‐based substrates, the coordination environment of SAs including the coordination mode and coordination strength directly influences the interaction between metal atoms and substrates.…”
Section: Constructing Strategies Of Environmental Sacssupporting
confidence: 62%
“…Recently, Yoon and colleagues synthesized thermally stable Pt‐CeO 2 nanoparticles with Pt SAs (up to 3–4 wt%) homogeneously distributed on CeO 2 and successfully implemented them as the electrode for a SOFC. The reported cell performance was greatly improved, outperforming the state‐of‐art Ni‐based fuel cell electrode 309 . They utilized symmetric cells to measure the electrochemical performance of Pt‐CeO 2 ‐infiltrated La 0.6 Sr 0.4 Cr 0.5 Mn 0.5 O 3−δ (LSCM) electrode where Pt‐CeO 2 nanocrystals uniformly deposited on the functional layer (Figure 10g) and found that Pt‐CeO 2 ‐LSCM electrode delivered the lowest polarization resistance at 600–800°C in comparison with blank LSCM and conversational Ni‐based electrode (Figure 10i).…”
Section: Applications In Energy Devicesmentioning
confidence: 99%
“…The reported cell performance was greatly improved, outperforming the state-of-art Ni-based fuel cell electrode. 309 They utilized symmetric cells to measure the electrochemical performance of Pt-CeO 2infiltrated La 0.6 Sr 0.4 Cr 0.5 Mn 0.5 O 3Àδ (LSCM) electrode where Pt-CeO 2 nanocrystals uniformly deposited on the functional layer (Figure 10g) and found that Pt-CeO 2 -LSCM electrode delivered the lowest polarization resistance at 600-800 C in comparison with blank LSCM and conversational Ni-based electrode (Figure 10i). The incorporation of Pt-CeO 2 reduced the polarization resistance of LSCM from 28.2 to 0.82 Ohm cm 2 at 600 C. In the interest of further identifying the contribution of Pt SAs, the electrode performances of LSCM infiltrated with CeO 2 , Pt NPs/CeO 2 and Pt-CeO 2 were evaluated and compared.…”
Section: Sofcsmentioning
confidence: 99%
“…Sr segregation induces low initial performance in SOFCs and results in continuous performance degradation. In the intermediate temperature (IT) region (500°C‐600°C), the cathode of SOFCs plays a vital role in most sluggish fuel‐cell reaction mechanisms and is known as the rate‐determining step 19‐21 . Therefore, it is crucial to maintain the intrinsic performance of the target perovskite cathode in the low‐temperature region while preventing the segregation of the cationic material at the A‐site.…”
Section: Introductionmentioning
confidence: 99%